Experimental and numerical characterization of mechanical properties of carbon/jute fabric reinforced epoxy hybrid composites - Ali, A. (Korean Society of Mechanical Engineers, 2019)
Natural fiber composites have great potential for reducing the product cost, lowering weight and enhancing renewability. Functionality and performance of natural fibers can be enhanced many folds using them together with synthetic fibers. Hybridization of carbon and low-cost natural jute fiber offers a sustainable hybrid composite having high modulus and mechanical strength. This study investigates flexural behavior of carbon/jute epoxy composites experimentally and numerically. Also, impact response is characterized through drop weight method. Study concludes that flexural strength decreases with increase in jute percentage. Simulation of flexural behavior diverges more than 10 from experimental results. This anomaly is due to waviness of fiber resulting in heterogeneous property distribution in composites. Further, the fracto-graphic study revealed modes of failure. The drop weight impact tests reveal increased damage area with increase in jute percentage. Â© 2019, KSME & Springer.